PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS APLIKASI TELEGRAM PADA PEMBELAJARAN IPA MATERI TATA SURYA - Hardiningrum, Esti Dwi; Djudin, Tomo; Nurdini, Asriah (Universitas Tanjungpura, 2023)
This study aims to determine the feasibility of animated video media based on the telegram application in science learning in grade VI Elementary School. This study uses a Borg and Gall research and development approach with nine development steps. The trial was carried out at SD Negeri 19 Sungai Raya in class VI. The research instrument is a validation questionnaire sheet and test questions. Based on the results of testing and validation, this product is valid and suitable for use in learning. The results of the validation analysis of material experts, media experts, student responses and class VI teachers stated that this product was valid and suitable for use after being revised. The results of the analysis of student achievement showed that there was an increase in learning outcomes after students used the product in learning. The learning outcomes of students after using this product are as many as 2 students with a